RESQ Banjir: a Mobile Apps for Emergency Rescue, Evacuation and Relief Center Management - Rafie Mohd Arshad, Muhammad; Hj Mohamed, Hasimah; Heikal Husin, Mohd; Hafinaz Hassan, Fadratul; Mohd Nazmee Wan Zainon, Wan; Rahim Ahmad, Abdul; Sabudin, Maziani; ., . (International Journal of Engineering and Technology, 2018)
A quick response to urgent relief needs after a natural disaster is vital to the alleviation of a disasterâ€™s impact in the affected areas. Flood victims had difficulties in sending emergency relief requests as they had limited phone battery life to highlight their current location.Â Such limitation led to the difficulty in locating the victims, which affected the effectiveness of coordinating a rescue and evacuation operation. In this research, we develop ResQ Banjir application which consists of Flood Rescue & Evacuation Operation Management (FREOM) and Flood Relief Centre Management (FRCM) to assist in flood disaster management. In these system, we exploits the existing and emerging technologies on smart phones and tablet such as sensors, cameras, GPS, SMS, Location Based System (LBS) and Augmented Reality (AR). The FREOM system is a web and mobile apps based system consist of the Rescue & Evacuation Management System (server) for rescue and evacuation operation monitoring & management at the flood operation center; SOS/SMS Flood apps for sending SOS help by victims; ResQ Banjir Skuad Penyelamat apps which is used by rescue teams to locate and rescue flood victims, and an Augmented Reality (AR) guidance system for location direction navigation guide. FRCM is a web based system which integrates a number of features such as flood relief center registry, shelter activation and management, inventory management and disbursement, and relief aid and goods supplies management.Â We conducted a simulation testing that involves the overall capability of the applications. Both systems seem to be working in an efficient manner although there are some issues that exist.Â Â